Laboratory bistatic synthetic aperture radar coherent change detection investigation - Hagelberg, Alexander; Andre, Daniel; Finnis, Mark V. (Institution of Engineering and Technology (IET), 2023)
Synthetic Aperture Radar (SAR) Coherent Change Detection (CCD) allows for the detection of very small scene changes. This is particularly useful for reconnaissance and surveillance as small changes such as vehicle tracks can be identified. In some situations, it is desirable to rapidly collect repeat pass SAR images for use in change detection, and multistatic geometries may facilitate this. Such repeat passes may however have significant baselines, particularly for satellite-based platforms, though CCD products are reliant on high coherence for good interpretability. This work investigates the sources and levels of incoherence associated with bistatic SAR imagery with increasing baselines using simulations and measured laboratory data.